The articulation between recent history of education and educational policy in the study of reforms: theoretical-methodological notes (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
The work proposes a theoretical-methodological approach to the study of educational reforms in recent history, which is a growing disciplinary field with its own identity within historiography. From there, two questions arise: what are the implications of investigating reform processes within the framework of recent history? And how does this dialogue with the theoretical references of other disciplines, such as educational policy? We use the toolbox of the history of education in relation to the recent past, especially the contributions of narrative and biographical-narrative studies (SUAREZ; OCHOA, 2007; PORTA, 2020; AGUIRRE; PORTA, 2019) in connection with the work on memory of the school (ESCOLANO, 1997) and institutional memory (MONTENEGRO, et al., 2018) as well as contributions of political sociology and, specifically, policy cycle studies (BALL, 1994) to reconstruct the reform processes as well as the effects on practices, institutions and subjects.Keywords: Reform. Recient history. Education Policy.